2022
DOI: 10.1111/vox.13238
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 outbreak on activation of the massive transfusion protocol in the emergency department

Abstract: Background and Objectives: An outbreak of coronavirus disease 2019 occurred in mid-May of 2021 in Taiwan. After 2 months of hard work, transmissions were successfully prevented and the number of newly confirmed COVID-19 cases fell remarkably. We evaluated the impact of this outbreak on the massive transfusion protocol (MTP) in the emergency department (ED) of a trauma centre. Materials and Methods:We retrospectively compared the activation and efficacy of MTP before, during and after the outbreak by analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The outbreak of coronavirus disease-19 (COVID-19) occurred in May 2021 in Taiwan, [21] profoundly affecting the efficacy of healthcare system and changing the healthproviding practice. [22][23][24][25] Fortunately, the outbreak was controlled with a series of prompt responses and interventions. During the COVID-19 pandemic, the healthcare system was overwhelmed with strained medical resources by a great many patients who required intensive care; and laboratory staff experienced exhaustion with a huge number of specimens for nucleic acid amplification and rapid antigen tests against severe acute respiratory syndrome coronavirus 2.…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak of coronavirus disease-19 (COVID-19) occurred in May 2021 in Taiwan, [21] profoundly affecting the efficacy of healthcare system and changing the healthproviding practice. [22][23][24][25] Fortunately, the outbreak was controlled with a series of prompt responses and interventions. During the COVID-19 pandemic, the healthcare system was overwhelmed with strained medical resources by a great many patients who required intensive care; and laboratory staff experienced exhaustion with a huge number of specimens for nucleic acid amplification and rapid antigen tests against severe acute respiratory syndrome coronavirus 2.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, which did not see the same increase in violent crime as the United States, there were no significant differences in frequency of massive transfusion protocol (MTP) triggers 21 . Although the same metric has not been studied directly in the United States, the relative increase in penetrating trauma did increase the percentage of trauma patients requiring transfusion 14 .…”
Section: Blood Product Availabilitymentioning
confidence: 97%
“…We thank Jacobs and colleagues for their comments on our article ‘The impact of the COVID‐19 outbreak on activation of the massive transfusion protocol in the emergency department’ [ 1 ]. Jacobs and colleagues found that half of the 50 surveyed institutions had no change of monthly massive transfusion protocol (MTP) activation in the previous study [ 2 ], which was similar to our results.…”
mentioning
confidence: 99%